Implications of late diagnosis of HIV/AIDS infection (Research, Society and Development, 2022)
The aim of the study was to identify in the literature the available evidence on the implications of delayed diagnosis of HIV/AIDS infection and discuss possible strategies for its reduction. This is an integrative review, using the following descriptors Delayed Diagnosis "AND" HIV Infection. controlled, keywords, synonyms and Boolean operators for database cross-referencing: which searched for primary studies in the National Library of Medicine PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL) and Latin American and Caribbean Health Sciences Literature (LILACS) databases. The late diagnosis of HIV involves individual factors, in which the patient feels embarrassed to share the subject with the health professional and family members, socioeconomic factors such as people with low education tend to assimilate the information inappropriately, making the apprehension of knowledge about the disease deficient and exposing individuals to vulnerability, The variable age, affecting people over 50 years, marital status and also the posture of health professionals who before the patient, do not address the issue sex in their consultation, so the knowledge of the high proportion of late diagnosis and associated factors are crucial to identify the new health demands presented by people living with HIV.